2022
DOI: 10.1371/journal.pone.0272156
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of the prevalence of unemployment and early retirement in people with multiple sclerosis: A systematic review with meta-analysis

Abstract: Background We aimed to summarise the prevalence of unemployment and early retirement among people with MS and analyze data according to a spatio-temporal perspective. Methods We undertook a systematic search of PubMed/MEDLINE, Scopus, SciVerse ScienceDirect, and Web of Science. We included any peer-reviewed original article reporting the prevalence of unemployment and early retirement in the working-age population with MS. We excluded articles off-topic, with other study designs, whose study sample were unli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 179 publications
(285 reference statements)
2
10
1
Order By: Relevance
“…Overall, the unemployment rate of 25% found in this cohort is below the pooled estimate of 35% provided by a recent meta-analysis, 6 which is likely explained by the lower severity of disability and shorter disease duration for participants in the CanProCo cohort, as well as the regional and temporal differences also outlined in the meta-analysis. As for productivity loss among the employed, results are consistent with those from our previously published study in a CanProCo sub-cohort.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Overall, the unemployment rate of 25% found in this cohort is below the pooled estimate of 35% provided by a recent meta-analysis, 6 which is likely explained by the lower severity of disability and shorter disease duration for participants in the CanProCo cohort, as well as the regional and temporal differences also outlined in the meta-analysis. As for productivity loss among the employed, results are consistent with those from our previously published study in a CanProCo sub-cohort.…”
Section: Discussioncontrasting
confidence: 80%
“…5 Even though there is some variability across countries and, in the last years, the proportion of unemployed pwMS has decreased (potentially related to advances in disease-modifying therapy (DMT)), pooled estimates for unemployment and early retirement remain 35.6% and 17.2%, respectively. 6 Furthermore, many pwMS that are still working experience substantial productivity losses even at low severity levels, as reported in our previous study in Canada, which showed an estimated 60 hours of productivity lost among employed pwMS during a 3-month period, including, presenteeism, absenteeism, and unpaid work loss. 7 The relationship among demographic, clinical, physical, and cognitive impairment factors and employment and work-related outcomes (including employment status, working hours, and productivity loss) have been studied previously.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…14 A recent systematic review also showed an overall decrease in the prevalence of unemployment among PwMS, attributed partly to the use of DMTs which was more pronounced since 2010, when the number of high-efficacy DMTs started to increase. 15 There is limited literature on the long-term DMT use trends and corresponding work disability measured with SADP days. In a recent register-based study, we assessed the trajectories of DMT use over 10 years from MS onset, using sequence analysis.…”
Section: Introductionmentioning
confidence: 99%
“… 14 A recent systematic review also showed an overall decrease in the prevalence of unemployment among PwMS, attributed partly to the use of DMTs which was more pronounced since 2010, when the number of high-efficacy DMTs started to increase. 15 …”
Section: Introductionmentioning
confidence: 99%